Figurative Language in Labrinth’s “Jealous”: A Critical Discourse Analysis and Its Pedagogical Applications in EFL Classrooms - Ihwanushofa, Jihad Wildan (Journey: Journal of English Language and Pedagogy, 2026)
This study investigates figurative language using Labrinth’s “Jealous” as the focal text in a multilingual educational context. Recognizing that traditional approaches in countries such as Indonesia often neglect the emotional and the cultural dimensions of language learning, this research proposes a pedagogical framework through Fairclough’s three-dimensional Critical Discourse Analysis (CDA) and derives conceptual pedagogical applications for multilingual EFL classrooms. The study systematically analyzes figurative devices across the selected lyrical units to identify their semantic, emotional, and cultural significance. The lyrics are segmented and analyzed for linguistic cues associated with metaphor, hyperbole, and other figurative language categories. Each expression then interpreted across textual, discursive, and sociocultural dimensions. The analysis shows how natural elements are metaphorically construed as rivals, emotional states such as emotional exclusion and loss are represented through metaphors, and hyperbole intensifies distance, misery, and concealed distress. These findings extend device-based analysis by explaining how figurative choices construct subject positions and relationship norms. Based on the analysis, the study proposes lyric annotation, guided discussion, role-play, classification, reflective writing, and optional digital activities. Because no classroom intervention or learner assessment was conducted, these activities are presented as pedagogical recommendations rather than validated strategies. Future research should evaluate their feasibility, cultural responsiveness, and learning effects in multilingual EFL settings.